Metabolite Profile of Marine Sponge (Stylissa sp.) Lipid Extract and Its Effect on Bacterial Skin Infection - Maulana, Farreh Alan; Utami, Ni Wayan Putri; Handayani, Ervina; Kabir, Mila Mayanti; Inggit, Baiq Putri Maharani Bine; Pangestu, Kukuh Waseso Jati; Deccati, Rizqa Fersiayana; Dewi, Ni Made Amelia Ratnata; Sunarwidhi, Anggit Listyacahyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
UV radiation from sunlight can induce the formation of free radicals, which can disrupt cellular homeostasis or DNA by triggering inflammatory signal transduction. The occurrence of inflammation in the skin can be aggravated by the presence of the bacterium Staphylococcus aureus. Previous studies have shown that the marine sponge Stylissa sp. contains an abundance of fatty acids and lipids compared to other species. Although Stylissa sp. has great potential for health applications, research on the bioactivity of lipid and fatty acid compounds from this sponge remains limited. Therefore, this study aims to explore the lipid content of Stylissa sp. as an alternative source of antibacterial agents against pathogens responsible for photoaging. The metabolite profiling of the extract was conducted using GC-MS, while the antibacterial activity was performed using the Kirby-Bauer method. Based on GC-MS profiling results, six compounds were identified in the lipid extract of Stylissa sp. namely palmitic acid, butyl glycol acetate, n-eicosylcyclohexane, isopropyl laurate, oleic acid, and 1-tetradecanol. Antibacterial evaluation of Stylissa sp. lipid extract at concentrations of 25%, 75%, and 100% showed antibacterial activity against Staphylococcus aureus, with inhibition zone diameters of 1.83, 2.17, and 2.92 mm, respectively. The results in this study have shown that the lipid extract of Stylissa sp. contains lipid compounds with potential anti-bacterial activity towards S. aureus. Future research to isolate unsaturated fatty acid compounds from the lipid extract of Stylissa sp. to achieve higher antibacterial activity is recommended.